Recognising foreign-accented speech of varying intelligibility and linguistic complexity: insights from older listeners with or without hearing loss. (1st February 2021) - Strori, Dorina; Bradlow, Ann R.; Souza, Pamela E.
Abstract: Objective: The goal of this study was to assess recognition of foreign-accented speech of varying intelligibility and linguistic complexity in older adults. It is important to understand the factors that influence the recognition of this commonly encountered type of speech, in a population that remains understudied in this regard. Design: A repeated measures design was used. Listeners repeated back linguistically simple and complex sentences heard in noise. The sentences were produced by three talkers of varying intelligibility: one native American English, one foreign-accented talker of high intelligibility and one foreign-accented talker of low intelligibility. Percentage word recognition in sentences was measured. Study sample: Twenty-five older listeners with a range of hearing thresholds participated. Results: We found a robust interaction between talker intelligibility and linguistic complexity. Recognition accuracy was higher for simple versus complex sentences, but only for the native and high intelligibility foreign-accented talkers. This pattern was present after effects of working memory capacity and hearing acuity were taken into consideration. Conclusion: Older listeners exhibit qualitatively different speech processing strategies for low versus high intelligibility foreign-accented talkers. Differences in recognition accuracy for words presented in simple versus in complex sentence contexts only emerged for speech over a threshold of intelligibility.